Gulnara Abikeyeva: Kazakhskaia novaia volna: Almaty: Tselinny Centre of Contemporary Culture, 2021, ISBN 978–601–06–7425–7, 400 pp. - Domashev, Nikolai (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2026)
The present review examines the book on the nature of the Kazakh New Wave edited by Gulnara Abikeyeva and provides an overview of how this cultural phenomenon entered the global scene. In particular, it discusses a number of factors that ensured the Kazakh New Wave’s rise to fame, including institutional support, rigorous training, and passionate practitioners.